The failures of functionalism (for memory) - Robins, Sarah (Estudios de Filosofía, 2021)
In Memory: A Self-Referential Account, Fernández offers a functionalist account of the metaphysics of memory, which is portrayed as presenting significant advantages over causal and narrative theories of memory. In this paper, I present a series of challenges for Fernández’s functionalism. There are issues with both the particulars of the account and the use of functionalism more generally. First, in characterizing the mnemonic role of episodic remembering, Fernández fails to make clear how the mental image type that plays this role should be identified. Second, I argue that a functionalist approach, which appeals to the overall structure of the memory system and tendencies of mental state types, is ill-suited to the metaphysical question about episodic remembering that is of interest to the causal and narrative theorists with which Fernandez engages. Fernández’s self-referential account of memory has many other virtues, but functionalism is a poor fit for episodic remembering.